User Acceptance Test Aplikasi Mobile SI CANTIK BANGSA untuk Pencatatan Kesetaraan Gender dalam Pembangunan Desa - Bahtiar, Arief Rais; Ramadhani, Rima Dias; Anto, Novri; Muna, Bunga Laelatul (Universitas Boyolali, 2024)
Gender equality is a complex issue that is difficult to eliminate in a society with a strong patriarchal culture. The Gender Empowerment Index (IDG) of Kebumen Regency decreased from 66.89% in 2021 to 66.86. The Kebumen Regency Government together with Institut Teknologi Telkom Purwokerto adopted the Si Cantik Bangsa Platform to support the activities of WANI LEmPER program cadres. This study aims to test the SI CANTIK BANGSA Mobile Application for recording gender equality in village development using the User Acceptance Test (UAT) method, namely alpha testing and beta testing. The results of alpha testing with the black box method show that all application modules are functioning properly. Beta testing using the System Usability Scale (SUS) resulted in an average score of 78.25, which means the application is acceptable with a grade C and an adjective rating of